2019
DOI: 10.1002/elps.201800412
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel multiplex polymerase chain reaction system for forensic individual identification using insertion/deletion polymorphisms

Abstract: Insertion/deletion (InDel) polymorphisms have been widely used in the fields of population genetics, genetic map constructions, and forensic investigations owing to the advantages of their low mutation rates, widespread distributions in the human genome, and small amplicon sizes. In order to provide more InDels with high discrimination power in Chinese populations, we selected and constructed one novel multiplex PCR‐InDel panel for forensic individual identification. Genetic distributions of these 35 InDels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Genotyping. In this study, the PCR amplification of 35 InDel loci was conducted on a GeneAmp PCR system 9700 thermal cycler (Applied Biosystems, Foster City, CA, USA), following previous descriptions [15]. en, the PCR amplification products were separated and detected by capillary electrophoresis on the ABI 3500 Genetic Analyzer (Applied Biosystems, Foster City, CA, USA).…”
Section: Pcr Amplification and Indelmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotyping. In this study, the PCR amplification of 35 InDel loci was conducted on a GeneAmp PCR system 9700 thermal cycler (Applied Biosystems, Foster City, CA, USA), following previous descriptions [15]. en, the PCR amplification products were separated and detected by capillary electrophoresis on the ABI 3500 Genetic Analyzer (Applied Biosystems, Foster City, CA, USA).…”
Section: Pcr Amplification and Indelmentioning
confidence: 99%
“…e reference populations of this study were the intercontinental populations [16] and Kazak group [15] reported before, which were African (7 populations), American (4 populations), East Asian (5 populations), European (5 populations), South Asian (5 populations), and Chinese Kazak group. Detailed information of these continental populations are as follows: African populations include ACB, ASW, ESN, GWD, LWK, MSL, and YRI; American populations include CLM, MXL, PEL, and PUR; East Asian populations include CDX, CHB, CHS, JPT, and KHV; European populations include CEU, FIN, GBR, IBS, and TSI; South Asian populations include GIH, ITU, PJL, STU, and BEB.…”
Section: Reference Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, DNA genotypes of DIP loci can be easily detected by capillary electrophoresis. Recently, forensic researchers developed some DIP panels for human identifications [15,16] or ancestry analyses [17,18]. To further enhance the discrimination power of DIP loci, Wendt et al assessed genetic variations in the flanking regions of 68 DIP loci by using the next generation sequencing (NGS) and found that these adjacent variations could improve forensic efficiency of the single DIP locus [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we searched potential polymorphic markers (SNP or DIP) in neighboring regions of previously reported SNPs and DIPs [5,[8][9][10][11]15]. Firstly, 23 novel genetic makers, including 10 microhaplotypes and 13 compound markers, were initially selected for forensic applications.…”
Section: Introductionmentioning
confidence: 99%